2022
DOI: 10.1016/j.jiac.2021.09.010
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine induced interstitial lung disease

Abstract: A 60-year-old man presented with dyspnea four days after the second dose of the coronavirus disease (COVID-19) vaccine. Imaging revealed extensive ground-glass opacification. Blood tests were notable for elevated KL-6 levels. Bronchoalveolar lavage fluid analysis showed increased lymphocyte-dominant inflammatory cells and decreased CD4/CD8 ratio. These findings were consistent with the diagnosis of drug-induced interstitial lung disease (DIILD). To the best of our knowledge, this has never been reported in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 14 publications
(21 reference statements)
3
31
2
1
Order By: Relevance
“…Cytotoxic injury to pneumocytes or the alveolar capillary endothelium may occur directly, whereas immune‐mediated reactions occur through T‐cell regulation 12 . In our patients, immune‐mediated reaction of the lung to the vaccine was suspected, based on the lymphocytic alveolitis in the BAL fluid or TBLC and efficacy of corticosteroids, consistent with previous studies 8,10,11 . Furthermore, both were Asian and had underlying ILD.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Cytotoxic injury to pneumocytes or the alveolar capillary endothelium may occur directly, whereas immune‐mediated reactions occur through T‐cell regulation 12 . In our patients, immune‐mediated reaction of the lung to the vaccine was suspected, based on the lymphocytic alveolitis in the BAL fluid or TBLC and efficacy of corticosteroids, consistent with previous studies 8,10,11 . Furthermore, both were Asian and had underlying ILD.…”
Section: Discussionsupporting
confidence: 84%
“…T A B L E 1 Clinical features of COVID-19 mRNA vaccine-related ILD and clinical outcomes Case Park et al 7 Yoshifuji et al 8 Kono et al 9 Shimizu et al 10 Shimizu et al 10 Shimizu et al 10 Matsuzaki et al…”
Section: Casementioning
confidence: 99%
“…Similarly, Khan et al also highlighted an ATM case after Moderna COVID-19 vaccination [14]. Likewise, cases of ILD after COVID-19 vaccines have also been reported [15]. Yoshifuji et al described a case of ILD after vaccination [15].…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, cases of ILD after COVID-19 vaccines have also been reported [15]. Yoshifuji et al described a case of ILD after vaccination [15]. Kono et al also reported a case of ILD after two weeks of COVID-19 immunization [16].…”
Section: Discussionmentioning
confidence: 98%
“…Post-marketing survey can provide important information on adverse reactions that were not known at the clinical trial, but it is insufficient to examine the details of individual cases. Only a few COVID-19 mRNA vaccine-associated ILDs have been reported in the literature [ [5] , [6] , [7] ].…”
Section: Discussionmentioning
confidence: 99%